Human Articular Chondrocytes Regulate Immune Response by Affecting Directly T Cell Proliferation and Indirectly Inhibiting Monocyte Differentiation to Professional Antigen-Presenting Cells - Pereira, Rui C.; Martinelli, Daniela; Cancedda, Ranieri; Gentili, Chiara; Poggi, Alessandro (Frontiers in Immunology, 2016)
Autologous Chondrocyte Implantation (ACI) is the current gold standard cell therapy for cartilage lesions. However, in some instances, the heavily compromised health of the patient can either impair or limit the recovery of the autologous chondrocytes and a satisfactory outcome of the implant. Allogeneic human articular chondrocytes (hAC) could be a good alternative, but the possible immunological incompatibility between recipient and hAC donor should be considered. Herein, we report that allogeneic hAC inhibited T lymphocyte response to antigen-dependent and independent proliferative stimuli. This effect was maximal when T cells and hAC were in contact and it was not relieved by the addition of exogenous lymphocyte growth factor interleukin (IL)-2. More important, hAC impaired the differentiation of peripheral blood monocytes induced with granulocyte monocyte colony stimulating factor (GM-CSF) and IL-4 (Mo) to professional antigen presenting cells (APC) such as dendritic cells (DC). Indeed, a marked inhibition of the onset of the CD1a expression and an ineffective down-regulation of CD14 antigens was observed in Mo-hAC co-cultures. Furthermore, compared to immature or mature DC, Mo from Mo-hAC co-cultures did not trigger an efficacious alloresponse. The prostaglandin (PG) E2 present in the Mo-hAC co-culture conditioned media is a putative candidate of the hAC-mediated inhibition of Mo maturation. Altogether, these findings indicate that allogeneic hAC inhibit, rather than, trigger immune response and strongly suggest that an efficient chondrocyte implantation could be possible also in an allogeneic setting.